The CDPK superfamily of protein kinases - Harmon, Alice C (The New phytologist, 2001)
The CDPK superfamily consists of six types of protein kinases, which differ in the regulatory domains they contain. CDPKs (calcium-dependent protein kinases or calmodulin-like domain protein kinases) are activated by the binding of calcium to their calmodulin-like regulatory domains. The carboxyl terminal domains of CRKs (CDPK-related kinases) have sequence similarity to the regulatory domains of CDPKs, but do not bind calcium. PPCKs (PEP carboxylase kinases) contain only a catalytic domain. PRKs (PPCK-related kinases) have a carboxyl-terminal domain that has no similarity to that of any other member of the superfamily. CCaMKs (calcium and calmodulin regulated kinases) bind both calcium ions and the calcium/calmodulin complex, whereas CaMKs (calmodulin-dependent protein kinases) bind the calcium/calmodulin complex, but not calcium. Phylogenetic trees constructed from amino acid sequences of catalytic or regulatory domains show that CDPKs and CRKs are closely related and might share a common ancestor. Plant CCaMKs and CaMK form a group more closely related to protozoan, than to plant, CDPKs. Intron analysis of the 42 CDPK, CRK, PPCK, and PRK genes from Arabidopsis supports the structure of the gene trees, the possibility that PPCKs/PRKs belong to the CDPK superfamily, and suggests that several introns have been added during evolution of the family